2021
DOI: 10.1108/ijpdlm-09-2019-0270
|View full text |Cite
|
Sign up to set email alerts
|

Packaging paradoxes in food supply chains: exploring characteristics, underlying reasons and management strategies

Abstract: PurposeThe purpose of this paper is to explore different types of packaging paradoxes and the reasons for their existence in food supply chains.Design/methodology/approachThe research uses a multiple case study approach with rich empirical data from seven leading companies in Swedish food supply chains. The research uses coding and a paradox theory lens to analyse packaging paradoxes, both within and between companies in a supply chain.FindingsThe paper provides a novel theoretical lens which uses comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Nonetheless, to achieve improved sustainable development outcomes, corporate leaders and managers must explore, embrace and address conflicting elements holistically (Sajjad et al , 2023). This finding resonates with the earlier studies focusing on investigating paradoxes and tensions managers encounter while addressing social, environmental and economic issues simultaneously in the plastic manufacturing context (Farrukh and Sajjad, 2023; Pålsson and Sandberg, 2022; Pålsson and Sandberg, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, to achieve improved sustainable development outcomes, corporate leaders and managers must explore, embrace and address conflicting elements holistically (Sajjad et al , 2023). This finding resonates with the earlier studies focusing on investigating paradoxes and tensions managers encounter while addressing social, environmental and economic issues simultaneously in the plastic manufacturing context (Farrukh and Sajjad, 2023; Pålsson and Sandberg, 2022; Pålsson and Sandberg, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the findings revealed that the FP companies are confronting the economic and operational barriers associated with the manufacturing of a variety of FP products, such as inventory management of different types of raw materials, which can lead to economic and environmental sustainability issues in the form of material waste, long setup times and energy consumption (Pa ˚lsson and Sandberg, 2021). The findings also indicated that the FP companies are facing issues of process and environmental waste, such as plastic waste and air emissions released during the processing of FP materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result depends on a set of tradeoffs emerging from our research, as well as the operational and logistical challenges that firms face whenever they seek to integrate environmentally sustainable practices into their operations (Pålsson and Sandberg, 2020, 2021). Furthermore, some practices may require coordination with external parties, making management even more difficult.…”
Section: Theoretical Insights and Managerial Implicationsmentioning
confidence: 99%
“…To answer this question, managers must recognize that they are dealing with a paradox, and rather than focusing solely on the business case, there is more to be gained-for all stakeholders-by identifying the options that provide utility for all (Hahn et al 2018;Chen et al 2021;Pålsson and Sandberg 2021).…”
Section: Csr Theorymentioning
confidence: 99%